The Biogeochemical Structure of Southern Ocean Mesoscale Eddies. Issue 8 (3rd August 2020) - Patel, Ramkrushnbhai S.; Llort, Joan; Strutton, Peter G.; Phillips, Helen E.; Moreau, Sebastien; Conde Pardo, Paula; Lenton, Andrew
Abstract: Mesoscale eddies play a key role in modulating physical and biogeochemical properties across the global ocean. They also play a central role in cross‐frontal transport of heat, freshwater, and carbon, especially in the Southern Ocean. However, the role that eddies play in the biogeochemical cycles is not yet well constrained, partly due to a lack of observations below the surface. Here, we use hydrographic data from two voyages, conducted in the austral summer and autumn, to document the vertical biogeochemical structure of two mesoscale cyclonic eddies and quantify the role of these eddies in the meridional transport of nutrients across the Subantarctic Front. Our study demonstrates that the nutrient distribution is largely driven by eddy dynamics, yielding identical eddy structure below the mixed layer in both seasons. This result allowed us to relate nutrient content to dynamic height and estimate the average transport by eddies across the Subantarctic Front. We found that relative to Subantarctic Zone waters, long‐lived cold‐core eddies carry nitrate anomalies of 1.6±0.2×10 10 moles and silicate anomalies of −5.5±0.7×10 10 moles across the fronts each year. This cross‐frontal transport of nutrients has negligible impact on Subantarctic Zone productivity; however, it has potential to modify the nutrient content of mode waters that are exported from the Southern Ocean to lower latitudes. Plain Language Summary: Mesoscale eddies are rotating bodies of water with diameters between 30 and 300 km that span weeks to months in the ocean. They are known to carry macronutrients (i.e., nitrate, silicate, and phosphate) across the Antarctic Circumpolar Current. Because of extremely limited direct observations of these eddies, it is difficult to calculate the actual quantity of nutrients that these eddies carry. Here we present new observations of two cold‐core eddies that we sampled during austral summer and austral autumn in the Southern Ocean south of Tasmania. We found that both eddies had similar nutrient distribution over their depth, especially below the mixed layer depth. Hence, this result motivated us to combine our observation with satellite observation to calculate the quantity of nutrients carried into the Subantarctic Zone by all the similar eddies. We found that eddies carried high‐nitrate and low‐silicate waters into the Subantarctic Zone. This transport has negligible impact on local biological production, but it has the capacity to change the nutrient content of waters that are exported from the Southern Ocean to lower latitudes. Key Points: The vertical biogeochemical structure of Southern Ocean cold‐core eddies is characterized from observations Below the mixed layer, eddy dynamics determined nutrient distribution and biological processes above the mixed layer Long‐lived cold‐core eddies carry high nitrate and low silicate across the Subantarctic Front south of Tasmania